Hypervelocity impact in low earth orbit: finding subtle impactor signatures on the Hubble Space Telescope. (2017) - Kearsley, A T; Colaux, J L; Ross, D K; Wozniakiewicz, P J; Gerlach, L; Anz-Meador, P; Griffin, T; Reed, B; Opiela, J; Palitsin, V V; Grime, G W; Webb, R P; et al.
Abstract: Return of materials from the Hubble Space Telescope (HST) during shuttle orbiter service missions has allowed inspection of large numbers of hypervelocity impact features from long exposure at about 615 km altitude in low Earth orbit (LEO) [1, 2]. Here we describe the application of advanced X-ray microanalysis techniques on scanning electron microscopes (SEM), microprobes and a 2 MV Tandetron, to nearly 400 impacts on the painted metal surface of the Wide Field and Planetary Camera 2 (WFPC2) radiator shield [3, 4]. We identified artificial Orbital Debris (OD) and natural Micrometeoroid (MM) origins for small [5] and even for larger particles [6], which usually may leave little or no detectable trace on HST solar arrays, as they penetrate through the full cell thickness [2, 7].